Major Trauma and Severe Burn: A Synergistic Mortality. Case Report and Literature Review - Pujol, Oriol; Selga, Jordi; Serracanta, Jordi; Porcel, Juan Antonio; Andrés-Peiró, José Vicente (Revista Chilena de Ortopedia y Traumatología, 2020)
Case Presentation A 42-year-old man was transferred to our institution after a high-energy accident (an explosion). He presented second-degree burns on 20% of the total body surface area (TBSA), affecting the lower hemiabdomen and the lower right limb. He also presented a supraintercondylar open fracture of the right femur (Gustilo I). The burns were treated with debridement and coverage with mesh graft, while the fracture required an early transitory transarticular external fixation with delayed definitive osteosynthesis. Our patient presented good local and systemic evolution. We can offer a eleven-month follow-up.Discussion The literature supports that the combination of trauma and burn injuries is a relatively rare pattern, which may explain the lack of knowledge and studies on this subject. This double injury has demonstrated a synergistic effect on mortality. The management of soft tissues in the coexistence of an open fracture and a burn in the same limb is a challenge. The method and timing of the treatment of the fracture directly impacts the treatment of the burn (and vice versa), and most authors tend to treat the fracture first. All of the studies reviewed emphasized the importance of the multidisciplinary approach.Conclusions We have presented a complex case combining major trauma and severe burns. Although there is a lack of studies in the literature on this subject, the papers state that this is an unusual pattern with a synergistic effect on mortality. In our experience, the management of soft tissues and the multidisciplinary approach play a central role, as it is also stated in the literature. The management of these patients is still controversial, and more studies are needed.
Keywords: burn; fracture; polytrauma; combined injury; soft tissue